Scanning electron microscopic study on freezing behaviour of tissue cells in dormant bud of mulberry (Morus sp.) - Choudhary, Ravish; Malik, SK; Chaudhury, Rekha; Pal, Digvender; Patel, Pravin; Sharma, KC (Bangladesh Journal of Botany, 2018)
The freezing behaviour studies of dormant buds, were examined, employing scanning electron microscopy (SEM) and light microscopy. The differences and effect of freezing behaviour on dormant buds were observed. The dormant bud primordia of several woody plant species avoid freezing injury by deep supercooling. By slow cooling (5°C/day) of dormant buds to –30°C, all living cells in bud tissues exhibited distinct shrinkage without intracellular ice formation detectable by SEM. However, the recrystallization experiment of these slowly cooled tissue cells, which was done by further freezing of slowly cooled buds with liquid nitrogen (LN) and then rewarming to –10°C, confirmed that some of the cells in the apical meristem, area in which cells had thin walls and in which no extracellular ice accumulated, lost freezable water with slow cooling to –30°C, indicating adaptation of these cells by deep super cooling. Water in plant tissues will not supercool unless heterogeneous ice nucleating substances are absent and the spread of ice from adjacent tissue can be prevented. Deep supercooling could not occur in dormant bud primordia if xylem vessels formed a continuous conduit connecting the dormant bud primordia with the remainder of the plant. If xylem continuity was established, ice could propagate via the vascular system and nucleate the water within the primordia. It is concluded that no extracellular ice crystals accumulated in such tissues containing deep supercooling cells with thin cell walls.